Heat Treatments Effects on the Fatigue Behaviors of Aluminum Nano-Composite Alloys - Al- Jaafari , Mamoon A. A. (Iraqi Journal of Science, 2021)
The fatigue is one of the major reasons for fracture of materials. Aluminum 7204 AA alloy with various heat treatments and (2.0) wt % of SiC nanoparticles were prepared by stir-casting method under rotating bending loading with ratio of stress (R= -1). The composite was strengthened by SiC particles size of) 10 (nanometre. The fatigue strength and life were obtained experimentally by the family of S-N curves for different heat treatments. The endurance limits (107cycles) for 7204 AA/ 2.0wt% SiC nano-composite fatigue strength as related to untreated nanocomposite was enhanced by 72 and 78.5% for T4 and T6, respectively.The improvement of fatigue properties is due to better spreading of SiC nanoparticles and increased porosity.